Testing the Web-Based Naive Bayes Classifier Method For Information on Skin Cancer in Humans: Testing the Web-Based Naive Bayes Classifier Method For Information on Skin Cancer in Humans - Raja Timor Purba; M. Iwan Wahyuddin; Ratih Titi Komalasari (Institute of Computer Science (IOCS), 2020)
The state of the earth is getting hotter give a lot of influence on the human body. One is a skin cancer, skin cancer caused by sun radiation is too much that it makes the skin cells to mutate. An expert system for finding information on the possibility of skin cancer that occurs as well as providing advice and how to cure this journal pakarpada .The system built with PHP and dataMySQL basis, the method used is Naive Bayes classifier, the method of classification using probability and statistics to predict the opportunities in future. The results of this study is to inform skin cancer with 80.00% accuracy results and provide saranterhadap possibility of skin cancer. Lock said skin cancer, Naive Bayes classifier, skin diseases, PHP, expert systems